Intestinal lymphangiectasia: case report - Aljohnei, Reham Mohmmad; Abdullah Alani, Hawazen Yousef (International Journal of Advances in Medicine, 2019)
Primary intestinal lymphangiectasia (PIL) was first described by Waldmann et al, in 1961. PIL is a rare disease with several hundred reported cases. It is rarely reported in adults because it is presumably a congenital disorder and when present in adults it typically produces a long duration of manifestation such as diarrhea, abdominal distention from ascites, and peripheral edema. This disorder is characterized by markedly dilated intestinal lymphatics, hypoproteinemia, generalized edema, lymphocytopenia hypogammaglobinemia, and immunologic anomalies. The loss of protein into the from dilated intestinal lymphatics leads to the development of hypoproteinemia in these patients and its demonstration is important in the diagnosis of intestinal lymphangiectasia. The disease can be secondary to congenital, secondary or idiopathic defects in the formation of the lymphatic ducts. In the present report, we describe a case of 15 years old female presented to our hospital with history of generalized edema, bilateral hand spasm, and diarrhea. Endoscopy of the patient revealed White spots (dilated lacteals), white nodules, and submucosal elevations were observed. Changes suggestive of the disease includes White villi and/or spots (dilated lacteals), white nodules, and submucosal elevations are observed. Xanthomata’s plaques are often visualized, there are no specific treatments for patients with PIL. treatment of patients with primary intestinal lymphangiectasia involves control of symptoms with the use of dietary, pharmaceutical, and behavioral modifications.